The ways of using of renewable energy sources in the territory of the Republic of Kazakhstan (Journal of Geography and Environmental Management, 2017)
For the territory of Kazakhstan the following types of alternative energy sources are most promising: solar energy, wind power, small hydroelectric power stations and others. In order to support the use of renewable energy sources, on July 4, 2009, the Law of the Republic of Kazakhstan «On Support for the Use of Renewable Energy Sources» was adopted. The law provides for a number of measures to support renewable energy sources, including: reservation and priority in the provision of land for the construction of renewable energy sources; Obligations of energy-transfer organizations for the purchase of electricity produced using renewable energy sources; The release of renewable energy sources from the charge for transporting electricity through networks; Support for the connection of facilities for the use of renewable energy sources to the networks of the energy transmission organization, provision to individuals and legal entities that carry out the design, construction and operation of facilities for the use of renewable energy sources, investment preferences in accordance with the legislation of the Republic of Kazakhstan on investments. The article considers all possible ways of introducing renewable sources of solutions in the territory of the Republic of Kazakhstan. Also, the research objects of the work are Astana Solar (Astana), ND-co (Almaty) and all other companies.